Political Agency and Public Health Care: Evidence from India - Joan Costa-i-Font; Divya Parmar (Center for Economic Studies and ifo Institute (CESifo), 2017)
A growing literature studies the effect of enhancing the agency relationship between political incumbents and constituents on the use of health care, and specifically maternal and preventive care services. We examine the development of institutions of self-governance in India, and specifically the 2005 reform—the National Rural Health Mission that introduced village health and sanitation committees—to study the effects of the strengthening of the political agency on collective health care decision-making in rural areas. We examine maternal and preventative child health care use, before and after the introduction of village health and sanitation committees. Our results suggest that the introduction of village health and sanitation committees increases access to several maternal health care and some but not all immunisation services. The effect size is larger in larger villages and those closer to district headquarters. Part of the effect is driven by an increase in the utilization of the public healthcare network.
Keywords: H70; I18; 330; decentralization; direct democracy; India; immunization; maternal healthcare; public health care; preventative health care